2016
DOI: 10.1007/s00114-016-1332-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel biodiversity baselines outpace models of fish distribution in Arctic waters

Abstract: During a recent marine biological expedition to the Northeast Greenland shelf break (latitudes 74-77 °N), we made the first discovery of Atlantic cod (Gadus morhua), beaked redfish (Sebastes mentella) and capelin (Mallotus villosus). Our novel observations shift the distribution range of Atlantic cod >1000 km further north in East Greenland waters. In light of climate change, we discuss physical forcing and putative connections between the faunas of the Northeast Greenland shelf and the Barents Sea. We emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…This opinion might possibly be based on fishermen visiting Greenland waters observing specific morphometric (phenotypic) characteristics of the cod growing up in Greenland waters that they recognize in Norwegian spawning sites. In a possible support, of considering the northeastern Greenland shelf as being a distant part of NEA cod habitat, are recent findings of adult cod in the area (Christiansen et al, 2016), see Figure 1.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This opinion might possibly be based on fishermen visiting Greenland waters observing specific morphometric (phenotypic) characteristics of the cod growing up in Greenland waters that they recognize in Norwegian spawning sites. In a possible support, of considering the northeastern Greenland shelf as being a distant part of NEA cod habitat, are recent findings of adult cod in the area (Christiansen et al, 2016), see Figure 1.…”
Section: Introductionmentioning
confidence: 88%
“…The thick black trajectory shows the 2009 drifter with arrival at the Greenland shelf as commented in section Connectivity Studies on Atlantic Cod. Locations of observed cod on Greenland are marked with green dots (taken from Christiansen et al, 2016). Currents are marked as NCC (green arrow), AW/NASC (red arrow), and Arctic water (blue arrow).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in fish distributions in the Arctic region have been found to be faster than predicted from models Ingvaldsen et al 2015;Christiansen et al 2016). The distributional changes are causing reconfigurations of ecological interactions in the Arctic (Kortsch et al 2015).…”
Section: Spatial Variation In Fish and Benthos Interactionsmentioning
confidence: 97%
“…Currently, changes in species distributions, interactions and food web structure in the Arctic cannot be predicted by models and data from regular large-scale surveys like the one used here are needed (e.g. Ingvaldsen et al 2015;Christiansen et al 2016).…”
Section: Spatial Variation In Fish and Benthos Interactionsmentioning
confidence: 99%
“…During a recent marine biological expedition, Christiansen et al (2016) made the first discovery of Atlantic cod on the Northeast Greenland Shelf break on the western side of Fram Strait. The observed cod were juveniles, and Christiansen et al (2016) found it conceivable that the individuals were advected with the Return Atlantic Current from the Barents Sea during their young pelagic phases.…”
Section: Implications and Future Workmentioning
confidence: 99%